2013
DOI: 10.1183/09031936.00145613
|View full text |Cite
|
Sign up to set email alerts
|

Differences in content and organisational aspects of pulmonary rehabilitation programmes

Abstract: The aim was to study the overall content and organisational aspects of pulmonary rehabilitation programmes from a global perspective in order to get an initial appraisal on the degree of heterogeneity worldwide.A 12-question survey on content and organisational aspects was completed by representatives of pulmonary rehabilitation programmes that had previously participated in the European Respiratory Society (ERS) COPD Audit. Moreover, all ERS members affiliated with the ERS Rehabilitation and Chronic Care and/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
198
0
24

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(230 citation statements)
references
References 37 publications
8
198
0
24
Order By: Relevance
“…Pulmonary rehabilitation programmes following acute exacerbation of COPD have effectively reduced readmission and mortality [28,29]. Moreover the inclusion of a number of interventions into a discharge care bundle [30,31] has also been shown to reduce readmission rates.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary rehabilitation programmes following acute exacerbation of COPD have effectively reduced readmission and mortality [28,29]. Moreover the inclusion of a number of interventions into a discharge care bundle [30,31] has also been shown to reduce readmission rates.…”
Section: Discussionmentioning
confidence: 99%
“…Surveys have suggested that the provision of pulmonary rehabilitation services can vary both within and between countries. 27 This highlights the need for pulmonary rehabilitation courses to be accredited and able to demonstrate adherence to the standards found in RCTs to be of maximum benefit to patients. This study also highlights the need for GPs to record completers of pulmonary rehabilitation for measurement of more accurate and meaningful outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Since financial resources for PR are often limited or even non-existing [4], identification of (clusters of ) patients that do (or do not) respond to PR will become necessary in the near future to improve its cost-effectiveness. This requires consensus about the key performance measures of PR services.…”
Section: Introductionmentioning
confidence: 99%